Sistem Demokrasi (Kebebasan Berpendapat) Masyarakat Di Indonesia Dalam Perspektif Sila Ke-4 - Jekson Saragih; Yakobus Ndano (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The Indonesian nation is a nation that adheres to the Pancasila philosophy, therefore every value in the Pancasila principles must be applied in national and state life. As the 4th principle of Pancasila states "The people are led by wisdom in deliberation/representation". This means that the principle of deliberation to reach consensus through representatives and representative bodies is put forward in fighting for the people's mandate. This view provides justification that democracy in this republic is carried out through an election mechanism (general election). In its implementation, democracy with people's sovereignty needs to be imbued and integrated with other principles, accompanied by a sense of responsibility to God Almighty, upholding human values ​​in accordance with human dignity, guaranteeing and strengthening national unity and used to realize social justice. . The existence of democracy with the spirit of Pancasila causes citizens to look at each other, respect, accept and cooperate in the form of unity for the common interests of "society" or "state".